A case of base rate bias, or are adolescents at a higher risk of developing complications after catheterizable urinary channel surgery?. Issue 2 (April 2017) - Szymanski, K.M.; Whittam, B.; Misseri, R.; Chan, K.H.; Flack, C.K.; Kaefer, M.; Rink, R.C.; Cain, M.P.
Summary: Objective: Adolescents are considered to be at high risk of developing complications after lower genitourinary tract reconstruction. This perception may be due to base rate bias, where clinicians favor specific information (adolescents with complications), while ignoring more general information (number of total adolescents being followed). The goal of this study was to assess whether age was a true risk factor for subfascial and stomal revisions after continent catheterizable urinary (CCU) channel procedures. Materials and Methods: Consecutive patients aged <21 years and who underwent appendicovesicostomy and Monti surgery at the present institution were retrospectively reviewed; demographic and surgical data were collected. Time to subfascial or stomal revision was stratified by age at initial surgery (child: <8, preteen: 8–12, adolescent: 13–17, adult: ≥18 years old) and analyzed with Cox proportional-hazards regression. Secondary analyses included: different age categories at initial surgery (<8, 8–11, 12–15, 16–19, ≥20 years), analyzing age as a continuous and a time-varying covariate. Results: Of the 510 patients with CCU channels (median age at surgery: 7.9 years), 63 (12.4%) had subfascial and 53 (10.4%) had stomal revision (median follow-up: 6.8 years). Median age at subfascial and stomal revision was 11.3 and 10.3 years, respectively. Preteens contributed 33.0% and adolescents contributed 29.3% of the total follow-up time (3263.9 person-years). Over 80% of revisions occurred within 5 years of surgery, regardless of age at initial surgery ( P ≥ 0.57) (Summary table). On multivariate analysis, age at initial surgery was not associated with undergoing subfascial ( P ≥ 0.62) or stomal revisions ( P ≥ 0.69). Montis were 2.1 times more likely than appendicovesicostomies to undergo a subfascial revision ( P = 0.03). No other variables were associated with the risk of subfascial or stomal revision ( P ≥ 0.11). Secondary analyses provided similar results. Discussion: Since the median age at surgery was 8 years old and most complications occurred within the first 5 years of follow-up, it is not surprising that most revisions occurred in 8–13 year olds. Pediatric urologists appear to base their impression of adolescents being "high risk" on specific information (adolescents having complications), while subconsciously ignoring more general information (adolescents represent a large proportion of patients in follow-up). This study had several limitations: channel complications treated non-surgically (e.g. prolonged catheterization) were not included. The findings may not be generalizable to other genitourinary reconstructive procedures or clinical settings. Conclusions: While complications were twice as high in Monti channels than appendicovesicostomies, no single age group was at increased risk. The impression that adolescents are a high-risk group appears to represent a base rate bias. Summary table Timing of subfascial and stomal revisions, stratified by age at surgery. Age at initial surgery Total revisions Revisions within the first 5 years of follow-up Subfascial revisions <8 years old 32 27 (84.4%) 8–12 years old 18 13 (72.2%) 13–17 years old 10 9 (90.0%) ≥18 years old 3 2 (66.7%) Stomal revisions <8 years old 27 23 (85.2%) 8–12 years old 17 15 (88.2%) 13–17 years old 7 7 (100.0%) ≥18 years old 2 2 (100.0%)